Not Only Environmental Conditions but Also Human Awareness Matters: A Successful Post-Crayfish Plague Reintroduction of the White-Clawed Crayfish (Austropotamobius pallipes) in Northern Italy - Manenti, Raoul; Barzaghi, Benedetta; Nessi, Alessandro; Cioccarelli, Sara; Villa, Mauro; Ficetola, Gentile Francesco (Frontiers in Ecology and Evolution, 2021)
In Europe invasive freshwater crayfishes are not only changing freshwater ecosystems, but they are also leading to local extinctions of native freshwater crayfishes. This is particularly evident for the populations of red swamp crayfish and spiny-cheek crayfish in Northern Italy, which are threatening the last and isolated populations of the white-clawed crayfish. Here we describe the steps that accompanied a successful reintroduction of the white-clawed crayfish in an Italian stream (Park Monte Barro) that, although isolated from other freshwater sites, suffered from an illegal introduction of the spiny-cheek crayfish in 2013. After the removal of presumably all the introduced spiny-cheek crayfish individuals, we started periodical surveys (twice a year) of the stream to confirm the absence of further introductions and monitor environmental conditions. Prior to the reintroduction of the white-clawed crayfish that started in autumn 2018, we developed an intense dissemination activity to raise awareness of white-clawed crayfish features and importance among the landowners surrounding the stream, including ones suspected of the introduction of the spiny-cheek crayfish: we organized public meetings and we performed seven direct visits, house by house, to the local people providing information on good practices for white-clawed crayfish conservation. From 2018 to 2020 every autumn we reintroduced a batch of three-month old white-clawed crayfish juveniles and we developed a program for the monitoring of crayfish growth and density, water quality, and direct landowners’ disturbance of the site. We detected a significant increase of the white-clawed crayfish total length from the first reintroduction (October 2018) to June 2020. In 2020, crayfish were consistently larger than in 2019 surveys; some of them were able to breed less than two years after the first reintroduction. In 2020 the estimated density of large crayfish reached 0.57 individuals/m2; this being lower than the density observed prior to extinction. We did not detect any case of human disturbance of the site. Our results underline that reintroduction actions could be more effective when the stakeholders with the greatest potential impact on the species are identified, informed and involved as primary caretakers of the activities.